Design of a supervisory algorithm based on failure mode effect criticality analysis for classification of different fault types of attitude determination sensors. (May 2019) - Abedi, Mostafa
In this paper, a supervisory algorithm for attitude determination sensors of a three-axis satellite is suggested to classify different fault types of this system. The presented solution is based on the computation of rotation matrices between the orbital and body frames. Using the Euler angles provided by these rotations, some variance measures are computed, which utilized as an analytical tool for the determination of faulty sensors and the related fault sources. According to the mentioned idea, it is shown that the fault sources could be categorized into four levels. Each level shows the fault extent and its criticality. To include the reliability aspects in this paper, a failure mode effect criticality analysis is conducted to determine different failure modes, which really occur in sensors. For this, the probability levels and the severity numbers were assigned to derive the critical ones. It is shown that most of the critical failure modes could be isolated by the proposed methods; in other words, the design process is based on real faulty scenarios that can improve the system reliability. Finally, by performing some numerical simulations, performance of the developed algorithms are validated.